2012
DOI: 10.1007/s00702-012-0869-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study methodologies to investigate genetic aspects and effects of drugs used in attention-deficit hyperactivity disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is one of the most common psychiatric disorders in children and adolescents, with up to 5 % affected worldwide. Twin and family studies on ADHD show its high familiality with heritability estimated around 70 %, but, to date, no specific polymorphism or gene was found to be specifically affected. Psychostimulants (amphetamine, methylphenidate) and non-psychostimulants (atomoxetine) are used successfully in ADHD therapy, but many of their mechanisms of action and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…PC12 cells, a cell line derived from a pheochromocytoma of the rat adrenal medulla, has been widely used as an in vitro experimental model to study Parkinson's disease (Pan et al, 2012; Xu et al, 2013), and ADHD (Grünblatt et al, 2013). PC12 cells are also used to study the effects of various neuroactive compounds such as cocaine (Shafer and Atchison, 1991; Imam et al, 2005), bromocriptine and quinpirole (dopamine D2 agonists) (Chiasson et al, 2006), himantane (antiparkinsonian drug) (Abaimov et al, 2008), 6‐hydroxydopamine (Xu et al, 2013), and MPH (Grünblatt et al, 2013; Bartl et al, 2010), since it is a dopaminergic neuronal cell and can synthesize, store, secrete, and take up DA (Pan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC12 cells, a cell line derived from a pheochromocytoma of the rat adrenal medulla, has been widely used as an in vitro experimental model to study Parkinson's disease (Pan et al, 2012; Xu et al, 2013), and ADHD (Grünblatt et al, 2013). PC12 cells are also used to study the effects of various neuroactive compounds such as cocaine (Shafer and Atchison, 1991; Imam et al, 2005), bromocriptine and quinpirole (dopamine D2 agonists) (Chiasson et al, 2006), himantane (antiparkinsonian drug) (Abaimov et al, 2008), 6‐hydroxydopamine (Xu et al, 2013), and MPH (Grünblatt et al, 2013; Bartl et al, 2010), since it is a dopaminergic neuronal cell and can synthesize, store, secrete, and take up DA (Pan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The MPH neuropharmacological profile is similar to amphetamine and cocaine (Challman and Lipsky, 2000), but the complete cellular effects of MPH are still unknown (Grünblatt et al, 2013; Gumustas et al, 2017). Functionally, MPH has been proposed as a high‐affinity inhibitor of dopamine (DA) and norepinephrine transporters, blocking the inward transport of DA and norepinephrine (Kuczenski and Segal, 2001; Volkow et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To show the effect of methylphenidate® on misdiagnosed children, studies have shown that this drug influences protein kinase B-mammalian target of rapamycin complex 1 signaling pathways (Akt-mTOR). PC12 cells, a cell line derived from a pheochromocytoma of the rat adrenal medulla, have been widely used as an in vitro experimental model to study ADHD (Grünblatt, Bartl, Marinova, & Walitza, 2013). These cells are also used to study the effects of methylphenidate® (Bartl et al, 2010;Grünblatt et al, 2013), since it is a dopaminergic neuronal cell that can synthesize, store, secrete, and take up DA (Pan, Zhu, Hwu, & Jankovic, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PC12 cells, a cell line derived from a pheochromocytoma of the rat adrenal medulla, have been widely used as an in vitro experimental model to study ADHD (Grünblatt, Bartl, Marinova, & Walitza, 2013). These cells are also used to study the effects of methylphenidate® (Bartl et al, 2010;Grünblatt et al, 2013), since it is a dopaminergic neuronal cell that can synthesize, store, secrete, and take up DA (Pan, Zhu, Hwu, & Jankovic, 2012). Based on that, the PC12 cells' response to methylphenidate® treatment was studied by analyzing Akt-mTOR pathway, as well as the mTOR substrates, 4E-BP1 and S6K kinase (Schmitz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Both non-neuronal and neuronal cell culture are useful for elucidating the genetic basis of a disorder and for assessing the pharmacologic effects of potential therapies at the cellular level. For instance, the toxicity, receptor binding and dopamine transport-inhibition properties of Ritalin have been measured in human and hamster cells, as well as the expression levels of the dopamine transporter gene variants associated with attention deficit hyperactivity disorder (ADHD) ( Grünblatt et al, 2013 ). At the level of neural circuits, the development of mammalian cortico-striatal cultures has facilitated analysis of synaptic activity.…”
Section: Cellular Tools For Psychiatric Disorder Researchmentioning
confidence: 99%